A study of Neospora caninum antibody seroprevalence ın dairy cows in Turkey - KASAP, S.; ERTUNC, S.; TEMIZEL, E. M.; SENTURK, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
Neospora caninum is a intracellular protozoan parasite and is one of the major causes of repeated abortions, foetal malformations, pre-term deliveries, stillbirth and possible loss of milk yield in livestock. The presence of specific antibodies against N. caninum in the blood serum of dairy cows is investigated in the present study. A total of 184 blood serum samples of dairy cows were examined in Bursa province in the Marmara Region. N. caninum antibodies were measured using an indirect enzyme-linked immunosorbent assay (ELISA) (The Svanovir Neospora-Ab ELISA). From the total sample, antibodies to N. caninum were detected in 62 of the 184 examined cows (33.3%) and neurological findings were seen in a calf.